Substrate-directed growth of n-heteropolycyclic molecules on a metal surface - Maaß, Friedrich; Stein, Arnulf; Kohl, Bernd; Hahn, Lena; Gade, Lutz H.; Mastalerz, Michael; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
N-Heteropolycyclic compounds are promising organic n-channel semiconductors for applications in field effect transistors. The adsorption behavior of these molecules on inorganic substrates is of great interest, since it affects the transport properties. Utilizing high-resolution electron energy-loss spectroscopy (HREELS) and density functional theory (DFT), we determined the adsorption geometry of three different N-heteropolycyclic molecules as a function of coverage on Au(111). All three π-conjugated aromatic molecules adopt a planar geometry with respect to the substrate in both the monolayer (ML) and thin films (up to 10 ML). Contrary, in their crystal structure the molecules are tilted up to 82° between the molecular planes in neighboring stacks. Electronic HREELS and DFT calculations allowed the determination of the optical gaps of the molecules which are unaffected by the nitrogen substitution of the polycyclic aromatic hydrocarbons, while the frontier orbitals of the N-heteropolycyclic compounds are stabilized. The present study provides important aspects such as adsorption and electronic properties which are essential for designing organic-molecules-based electronic devices.
Gesehen am 22.05.2020